The Reproductive Outcome of Women with Hypogonadotropic Hypogonadism in IVF - Zhang, Chun-mei; Zhang, Hua; Yang, Rui; Chen, Li-xue; Liu, Ping; Li, Rong; Qiao, Jie; Wang, Ying (Frontiers in Endocrinology, 2022)
Objective: The purpose of this study was to evaluate the reproductive outcome of patients with hypogonadotropic hypogonadism (HH) receiving in vitro fertilization and embryo transfer (IVF-ET). Methods: The reproductive outcome of 81 HH patients and 112 controls who underwent oocyte retrieval was evaluated retrospectively in the Center for Reproductive Medicine of Peking University Third Hospital from 2010 to 2019. Results: The basic levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), androstenedione (A) and prolactin (PRL) were significantly lower in the HH group than the control group. Although the HH patients required a significantly longer stimulation and higher gonadotropin (Gn) doses than the control patients, the total number of oocytes retrieved, fertilized embryos, two pronuclear (2PN) embryos, transferable embryos, fertilization and 2PN rates were comparable between the two groups. Although the live birth rate (LBR) of the first fresh cycle was higher in the control group than the HH group, there was no statistical significance. Then we further divided HH patients into two subgroups according to the etiology. Forty-one cases were termed as congenital HH (CHH), while the other 40 cases were termed as acquired HH (AHH), the latter includes functional hypothalamic amenorrhea (FHA) and pituitary HH (PHH). Our results showed that there were no significant differences in basic clinical characteristics and IVF parameters between the two groups. In the HH group, a total of 119 oocyte retrieval cycles were carried out and they responded adequately to ovulation induction. Urinary human menopausal gonadotropin (HMG) was used alone in 90 cycles while combination of HMG and recombinant human follicle stimulating hormone (rFSH) in the other 29 cycles. There were no significant differences in IVF-related parameters between the two groups. The conservative cumulative live birth rates (CLBRs) after the first, the second and ≥third cycles were 43.21%, 58.02% and 60.49%, , respectively, while the corresponding optimal CLBRs were 43.21%, 68.45% and 74.19%. The preterm birth (PTB) rates of singletons and twin pregnancy in HH patients were 8.33% (3/36) and 30.77% (4/13), respectively. Conclusion: IVF-ET is an effective treatment for HH patients with infertility and patients can get satisfactory pregnancy outcomes.